EUROPEAN PAEDIATRIC ONCOLOGY OFF-PATENT MEDICINES CONSORTIUM (EPOC): A PHARMACOKINETIC STUDY OF DOXORUBICIN IN CHILDREN WITH CANCER. Issue 1 (14th December 2015) - Krischke, Miriam; Boddy, Alan V; Hempel, Georg; Völler, Swantje; André, Nicolas; D'Incalci, Mauricio
Abstract : Background: Doxorubicin is a key component of a number of treatment regimens used in paediatric oncology. The pharmacology data on which current dosing regimens are based are very limited. Methods: We conducted a multicentre, multinational pharmacokinetic study investigating age-dependency in the clearance of doxorubicin in children with solid tumours and leukaemia. Blood samples for measurement of doxorubicin and its metabolite doxorubicinol were collected after 2 administrations, with 5 samples collected in children 3 yrs. A population pharmacokinetic approach was used for analysis, including pharmacogenetic covariates. NT-proBNP and cardiac troponin T were measured to evaluate their role as early indicators of cardiotoxicity. Results: 101 children could be recruited including 27 patients less than 3 years and among those 5 infants younger than 1 year. Overall, the patient acceptance of the trial was very good. Age dependence of doxorubicin clearance was demonstrated, with children less than 3 years having a lower clearance (21.1±5.8 l/h/m2) than older children (26.6±6.7 l/h/m2) (p=0.0004), after correcting for body weight. Pharmacogenetic variants, including those in transporters and drug metabolizing enzymes, had little influence on pharmacokinetic parameters. Natriuretic peptides plasma levels increased significantly shortly after doxorubicin administration, whereas cardiac troponin levels increased only with the administered cumulative anthracycline dose. Only limited correlation could be observed between their blood levels and doxorubicin pharmacokinetics. Conclusion: The paediatric need concerning missing PK-data could be addressed with limited burden for the patients. Empirically used dose adaptations for infants were found to be justified based on our PK analyses.